Social Relationship as a Factor for the Development of Stress Incubation in Adult Mice - Lee, Ray X.; Stephens, Greg J.; Kuhn, Bernd (Frontiers in Behavioral Neuroscience, 2022)
While stress reactions can emerge long after the triggering event, it remains elusive how they emerge after a protracted, seemingly stress-free period during which stress incubates. Here, we study the behavioral development in mice isolated after observing an aggressive encounter inflicted upon their pair-housed partners. We developed a spatially resolved fine-scale behavioral analysis and applied it to standard behavioral tests. It reveals that the seemingly sudden behavioral changes developed gradually. These behavioral changes were not observed if the aggressive encounter happened to a stranger mouse, suggesting that social bonding is a prerequisite for stress incubation in this paradigm. This finding was corroborated by hemisphere-specific morphological changes in cortex regions centering at the anterior cingulate cortex, a cognitive and emotional center. Our non-invasive analytical methods to capture informative behavioral details may have applications beyond laboratory animals.